Patient-reported outcomes of patients with myelofibrosis or essential thrombocythemia enrolled in the MOST study. Issue 13 (10th November 2022) - Ritchie, Ellen; Al-Janadi, Anas; Kessler, Craig; Scherber, Robyn; Kalafut, Tricia; Ren, Haobo; Mesa, Ruben
Abstract: The Myelofibrosis and Essential Thrombocythemia Observational STudy (MOST; NCT02953704) is an ongoing, noninterventional study assessing clinical characteristics and patient-reported outcomes (PROs) of patients with myelofibrosis (MF) or essential thrombocythemia (ET). This analysis assessed PROs at enrollment; symptom burden and quality of life (QoL), work productivity, and activity were assessed using validated questionnaires in patients with low- or intermediate-1-risk (age-alone) MF, or high- or low-risk ET (receiving ET-directed therapy) at enrollment. In MF and ET cohorts, fatigue had highest mean symptom score. Women had higher mean total symptom scores (TSS), mean symptom scores, and reduced QoL versus men. In patients with MF, mean TSS and symptom scores were similar between risk groups. Patients with low-risk ET had higher mean TSS and symptom scores than patients with high-risk ET. In conclusion, patients with lower risk MF and low- or high-risk ET experience significant symptom burden affecting QoL and ability to work.